Naturally occurring anti M complicating ABO grouping - Safoorah Khalid; Roelyn Dantes; Sunu Varghese; Imadeddin Al Hakawati (Wolters Kluwer Medknow Publications, 2011)
Anti M is considered a naturally occurring antibody that is usually active at temperatures below 37°C and is thus of no clinical significance. This antibody, if present in an individual, can lead to a discrepancy between forward and reverse ABO grouping and thus creates diagnostic difficulties for blood bank staff. We report a case of a 58-year-old lady who had an unexpected reaction in reverse grouping due to anti M that posed a problem for us in the interpretation of results of her blood group. We also reviewed the literature to find out the significance of such discrepancy in blood grouping.